Relações causais entre a expressão dos genes do receptor de Vitamina D e do Peptídeo Antimicrobiano Catelicidina sobre marcadores sorológicos de pessoas com Hanseníase antes e após seis meses de Tratamento Poliquimioterápico - Ana Laura Grossi de Oliveira (2020)
Background: Leprosy is determined by the modulation of the host's immune response to infection by Mycobacterium leprae and gene expression changes may be determinant of the disease’s prognosis. Objectives: To establish and quantify the causal relationships between the expression of the genes of the vitamin D receptor (VDR) and the cathelicidin antimicrobial peptide (CAMP) and their effects on the vitamin D, cathelicidin and cytokines serum levels in untreated leprosy patients before and after six months of multidrug therapy (MDT) and household contacts. Methods: Biological samples from 34 leprosy patients, consisting of paucibacillary (PB; n = 14) and multibacillary (MB; n = 20), before and after six months of MDT, were analyzed, as well as 18 healthy controls and 25 household contacts. Vitamin D, cytokines and cathelicidin serum levels were quantified by high performance liquid chromatography (HPLC), flow cytometry and enzyme-linked immunosorbent assay (ELISA), respectively. Gene expression analyzes were performed using real-time quantitative polymerase chain reaction (RT-qPCR). A Pearson correlation matrix was calculated to assess the association between the main variables. Finally, a path analysis was elaborated to verify causal relationships involving VDR and CAMP gene expressions, having as direct and indirect effects the vitamin D, cathelicidin and cytokines serum levels. Results: The direct and indirect effects of both gene expressions for the untreated leprosy group correlated with the IL-2 to PB and MB. After six-month of treatment, the probable immunological pathways suggest induction of IL-17F for the PB, and, for MB, IFN-, supported by other interactions between IL-2, IL-6, IL-17A, IL-17F and IL-21. For the control group, there was a direct correlation between CAMP gene expression over IFN-, while for household contacts, no correlations were observed. Conclusion: Path analysis showed that both PB and MB patients use an immunological pathway dependent on the association of VDR and CAMP gene expression to regulate IL-2 serum levels; and that after six months of MDT, these pathways became more complex, involving Th1 and Th17 cytokines to eliminate the bacillus and control leprosy.